Aerodynamic Test of AGARD-B Model at Mach 10 in Arc-heated High-Enthalpy Wind Tunnel - Tingting ZHANG; Jian LIN; Yue GUO; Huazhen SONG; Feng JI (气体物理)
The test capacity of hypersonic equipment is crucial to the development of hypersonic technology. However, the maximum Mach number simulated by conventional hypersonic wind tunnel is less than 10 currently due to the insufficient heater capacity. Considering the outstanding performance of arc heater in high-enthalpy wind tunnel, applying arc-heated high-enthalpy wind tunnel for conventional aerodynamic tests makes a breakthrough for increasing test Mach numbers. This paper presented the test of AGARD-B calibration model carried out in the arc-heated high-enthalpy wind tunnel of the China Academy of Aerospace Aerodynamics. The standard deviation of multiple repeated aerodynamic test results verified the self-consistency of test data and proved the stability of flow field. Accuracy of the test data was also certified through comparison and analysis with existing data from both foreign and domestic wind tunnels. This test demonstrated that the arc-heated high-enthalpy wind tunnel is fully capable of conducting aerodynamic tests at Mach 10.